Nanoparticles-in-beads made of alginate and chitosan derivatives as oral insulin carrier / Mulham Alfatama - Alfatama, Mulham (2017)
This project aimed to design nanoparticles-in-beads made of alginate, chitosan and their derivatives as oral insulin carrier. In the first part of the study, the calcium alginate beads were prepared using the vibratory nozzle extrusion microencapsulation technique through concurrent core and coat formation with chlorpheniramine maleate as a model drug. These beads were coated with chitosan/chitosan-oleic acid conjugate of which the latter was synthesized via covalent reaction. The formability of beads was optimized through varying alginate solution concentration, alginate/chitosan solution flow rate and nozzle vibrational frequency. The size, shape, morphology, swelling, erosion, water uptake, drug content, drug release and matrix molecular profiles of beads were characterized. Spherical discrete coated beads were produced through critical interplay of nozzle vibrational frequency and polymeric solution flow rate.